Indirect Network Effect and Spillover Effect in Food Delivery Platforms - GONG LEE (KDI Journal of Economic Policy, 2022)
I analyze how the food delivery market’s indirect network effect and spillover effect influence the spread of food delivery platforms in different counties. This study finds that there is a positive local indirect network effect and a positive spillover effect in the adoption of the platform by examining the food delivery platform market in South Korea as of 2020. As food delivery platforms secure consumers who use them, more restaurants on the other side of a two-sided market adopt such platforms (indirect network effect). The spillover effect would allow other restaurants in a region to become more likely to adopt food delivery platforms if there are a greater number of restaurants in the region that use such platforms. This study contributes to the comprehension of technology diffusion and the marketing strategies of platform providers by providing empirical evidence of both effects.